Opening Ceremony Est. 2002 - Lim, Carol; Leon, Humberto (Rizzoli, 2012)
This lively volume celebrates the contributions to inventive fashionable living by the New York, based style innovator, Opening Ceremony, a bible for the fashion-forward and culturally savvy alike. In 2002, when Carol Lim and Humberto Leon opened the downtown Manhattan retail shop Opening Ceremony, they created what has become the most innovative fashion and culture destination in New York. Bringing together the best emerging American talent with international designers and historic brands, Opening Ceremony represents the best in fashion and has played a vital role in launching the careers of many young designers. Celebrating the companies tenth anniversary, Opening Ceremony is a visually rich documentation of Leon and Lim's diverse inspirations, collaborators, and creative community, including Ryan McGinley, Rodarte, and Alexander Wang. A celebratory look at New York's quintessential style headquarters, this book will captivate and inspire readers from fashion, art, music, film, and beyond